Tradition, Social Solidarity, Religion and Culture: Tradisi berzanji dan Pengaruh terhadap masyarakat Desa Salakbrojo - Zidniyatul Hidayah (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2022)
Tradition, social solidarity, religion and culture The tradition of reading the book of Barzanji has actually been practiced for a long time in Muslim society. The existence of the tradition of zanji in society can increase solidarity so as to create good friendship and facilitate the broadcasting of Islam to the community. The tradition of reading the book of barzanji is an activity that is usually carried out once a week and every time there is a thanksgiving event. The purpose of this research is to examine and examine the barzanji tradition in increasing solidarity and its influence in the village of Salakbrojo. This study applies a qualitative approach with a descriptive method. The method of analyzing data is based on explanations from primary and secondary data. The results of the study prove the tradition of reading the book of Barzanji Salakbrojo which is based on the solidarity of the whole community. The existing solidarity is created in the form of togetherness regardless of social class and collaboration between communities in protecting the existence of the barzanji tradition to this day.Tradition, social solidarity, religion and culture The tradition of reading the book of Barzanji has actually been practiced for a long time in Muslim society. The existence of the tradition of zanji in society can increase solidarity so as to create good friendship and facilitate the broadcasting of Islam to the community. The tradition of reading the book of barzanji is an activity that is usually carried out once a week and every time there is a thanksgiving event. The purpose of this research is to examine and examine the barzanji tradition in increasing solidarity and its influence in the village of Salakbrojo. This study applies a qualitative approach with a descriptive method. The method of analyzing data is based on explanations from primary and secondary data. The results of the study prove the tradition of reading the book of Barzanji Salakbrojo which is based on the solidarity of the whole community. The existing solidarity is created in the form of togetherness regardless of social class and collaboration between communities in protecting the existence of the barzanji tradition to this day.